Becoming a Meaningful Human in The Contemporary Era: Isyari's Interpretation of Human Fiṭrah in Risālah Al-Nūr According to Said Nursi - Zaimul Asroor; Cemal Sahin (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2020)
This paper wants to prove how Said Nursi's efforts to persuade humans to become meaningful (ma’nawi) humans through his interpretation of Risālah al-Nūr. This tafsir, which is more Kalam and Isyāri (Sufi) in style, was Nursi's answer to his anxiety in facing the challenges of modernity in Turkey at that time (and is still relevant today). In the context of human nature, Nursi is aware that modernity has made humans fall into an attitude which he calls tafrid and ifrat in using his every senses (outer and inner senses). Therefore, with the characteristics and originality of his interpretation, he describes how people can return to their nature, namely by behaving 'adl or tawasut in all things. This is the man that he later calls as a meaningful human being. The methods that the author used in this research are descriptive-analysis methods and library research, by making tafsir Risālah al-Nūr and tafsir Isyārāt al-I’jāz as primary sources, then supported by other secondary books which are still related to the theme.